IMPLEMENTING “RATIONAL DRUG USE PROVINCE” POLICY THROUGH SYSTEMS GOVERNANCE: A QUALITATIVE RESEARCH - Suwannaprom, Puckwipa; Suttajit, Siritree; Pumtong, Somying; Tomacha, Nucharin; Puripunyavanich, Naphaphorn; Chowwanapoonpohn, Hathaikan (Thai Bulletin of Pharmaceutical Sciences, 2023)
Promoting rational drug use at the provincial level (RDU Province) is leverage to achieve the national goal of a rational drug use country (RDU Country). This qualitative research analyzed mechanisms to reach the RDU province as a concept within health systems governance. Nine provinces that continuously demonstrated development in RDU implementation were selected for this research. Key participants were pharmacists and their teams who were responsible for RDU implementation in steering the work at the district and provincial levels. Data was collected from group interviews via Zoom application and thematically analyzed through 5 functions of the health systems governance. The results revealed that RDU province was implemented through the following activities. 1) Policy guidance: the provinces have set clear policies, goals and performance indicators on RDU. 2) System design for implementing the policies: several mechanisms were used, such as having a provincial leader chair the RDU committee, joining RDU activities with other relevant committees, continuously and consistently presenting situations of RDU performance to executives and practitioners, communicating to clarify policies, and integrating RDU work with routine work. 3) Generating intelligence was strenghtened by using data to drive the countinuous quality improvement process, cultivating a culture of data-driven decision-making, and organizing a knowledge-exchange forum. 4) Building collaborations and partnerships were conducted through local committees on quality of life development with cooperation of community leaders and public sector networks. 5) Ensuring accountability was carried out by developing a transparent working system that can be reviewed and assessed from other sectors.